The Influence of Teacher Pedagogical Competence and Learning Facilities on Student Learning Outcomes in Economics Subjects - Wulandari, Yeni; Uwameiye, Bridget (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The aim of this research is to determine the influence of teacher pedagogical competence and learning facilities on student learning outcomes in economics subjects. Methodology: The research method used is a quantitative descriptive method. The population as subjects in this research were class XI students majoring in social sciences at high school. The sampling technique used in this research was proportional random sampling. The number of samples in this study was 127 respondents. The data collection techniques used were questionnaires and documentation. Data on pedagogical competence and student learning facilities were obtained from the results of distributing questionnaires with a Likert scale. The data analysis technique used is multiple linear regression. Main Findings: Based on the research results, it can be concluded that there is a significant positive influence between pedagogical competence and learning facilities on learning outcomes (F calculated > F table or 14.996 > 3.07 at the 5% significance level) and the coefficient of determination is 19.5%. This means that the influence of pedagogical competence and learning facilities on student learning outcomes is 19.5%, while it is influenced by other factors at 80.5%. Novelty/Originality of this study: The novelty of this research is that it strengthens the theory about the magnitude of the influence of teacher pedagogical competence and learning facilities in determining student learning outcomes.